FACTORS AFFECTING WOMEN'SCAREER CHOICE AND SELF-EFFICACY: EVIDENCE FROM KHYBER PAKHTUNKHWA, PAKISTAN - Ullah, Farman; Yahya, Salman (Journal of Business & Tourism, 2022)
The research is based on the women's career choices in Khyber Pakhtunkhwa.The main focus of the research is to judge the perception that women of Peshawar hold about different occupations, her choice of choosing her career, and to which extent she is influential in choosing her career. The study is carried out in Khyber Pakhtunkhwa, especially Peshawar. Data is primary, and descriptive statistics are being used on the questionnaire.Two portion questionnaires are developed for the study. The study suggests that fathers influence female career choices. Most of the females in the telecom sector and Khyber Pakhtunkhwa prefer job security in the job sector.